The effect of A5TB refiner on the fatigue strength of 6063Al alloy (2010)
The study focuses on the influence of aluminium titantium boron (ASTB) master alloy on the fatigue behaviour at 6063Al alloy. Cylindrical cast rods of 6063Al containing different proportions of A5TB ranging from 0-0.11 wt% were produced and were machined to conform to a standard fatigue specimen. The test specimens prepared were tested for fatique strength at various stress levels, and results obtained were compared. The resistance to fatique failure was observed to decrease as the stress level increased. It was also noted that irrespective of stress level, the optimum fatique strength was obtained when the A5TB content was about 0.06 wt%. It was found that 6063Al alloy to which A5TB master alloy have been added was most suitable for the design of components meant to operate under cyclic loading at low stresses below about 3.02KN/m2.